2019
DOI: 10.3390/e21121163
|View full text |Cite
|
Sign up to set email alerts
|

Application of Data Mining for the Prediction of Mortality and Occurrence of Complications for Gastric Cancer Patients

Abstract: The development of malign cells that can grow in any part of the stomach, known as gastric cancer, is one of the most common causes of death worldwide. In order to increase the survival rate in patients with this condition, it is essential to improve the decision-making process leading to a better and more efficient selection of treatment strategies. Nowadays, with the large amount of information present in hospital institutions, it is possible to use data mining algorithms to improve the healthcare delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 37 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Machine learning and Data Mining (DM) are becoming increasingly important areas of engineering and computer science and have been successfully applied to a wide range of problems in science and engineering [34,35]. Machine Learning is the scientific field dealing with the construction of computer systems that have the ability to adapt, learn and improve their performance in a given domain through experience.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning and Data Mining (DM) are becoming increasingly important areas of engineering and computer science and have been successfully applied to a wide range of problems in science and engineering [34,35]. Machine Learning is the scientific field dealing with the construction of computer systems that have the ability to adapt, learn and improve their performance in a given domain through experience.…”
Section: Methodsmentioning
confidence: 99%
“…The useful trends will allow us to make nontrivial predictions about new data and are insightful in many significant ways about the already-observed data. However, to make matters worse, it is not always simple to identify these trends [26] [27].To succeed, we will have to use more sophisticated means of representing these systemic trends in results.…”
Section: Data Mining Implications In the Healthcare Sectormentioning
confidence: 99%
“…According to one study, 44,000 to 98,000 people die in the United States each year due to preventable medical errors (which account for 2-4% of all medical fatalities). Separate research found that up to 40% of patients were not receiving the appropriate treatment for chronic or acute illnesses [26].…”
Section: Limitations Of Data Mining In Healthcare Sectormentioning
confidence: 99%
“…Data mining is a successful tool for extracting knowledge from large amounts of data. It is efficiently applied to many fields, such as weather forecasting [1], biomedical [2], medical diagnosis [3], marketing [4], security [5], and fraud detection [6]. On the other hand, sensitive data used in data mining applications or sensitive knowledge gained from these applications may cause privacy breaches directly or through linkable private data.…”
Section: Introductionmentioning
confidence: 99%